Matched-Pair Analysis of Magnetic Resonance Images for Location of the Common Peroneal Nerve in Valgus Knees: Comparison with the Varus Knees - Jung, Kwang Am; Shon, Oog-Jin; Banday, Mohd Irfan; Patil, Abhishek; Kim, Gi Beom (The Journal of Knee Surgery, 2020)
This study aimed to assess the distance and angular location of the common peroneal nerve (CPN) on axial magnetic resonance imaging (MRI) in the valgus knees and compare the measurements with those obtained from the control group. We compared the location of the CPN according to the type of alignment by performing a subgroup analysis. From January 2009 to December 2019, we identified 41 knees with preoperative MRI in patients who underwent total knee arthroplasty (TKA) for valgus deformity (valgus group). We performed one-to-two matched-pair analysis to a cohort of patients who underwent MRI but were not candidates for TKA (control group), according to sex and age. The valgus group was classified according to the grading system reported by Ranawat et al, and the control group was also subdivided according to the hip-knee-ankle (HKA) angle obtained from lower extremity scanography: neutral (–3 to +3 degrees from the neutral mechanical axis), valgus (> +3 degrees), and varus alignment (< –3 degrees). Distance between the CPN and posterolateral cortex of the tibia at the knee joint (distance J) and tibial cut level (distance C) were measured. Angle of the CPN from the central anteroposterior axis of the tibia (angle α) was measured. We compared the measurements between the groups. Distance J was significantly closer in the valgus group (p < 0.001), whereas angle α was significantly smaller in the valgus group (p < 0.001). However, no significant differences were found in the subgroup analysis. Moreover, a significant correlation was found between distance J and the HKA angle (p < 0.001). The location of the CPN in the valgus knees was closer to the posterolateral cortex of the tibia at the joint level and showed a smaller angle than that in the other aligned knees. We recommend that lateral soft tissue release for valgus knees should not be performed at the joint line. The results of this study suggest that this would be less safe than a release performed at the level of the proximal tibial bone resection.
Keywords: common peroneal nerve; magnetic resonance image; valgus knee; total knee arthroplasty; osteoarthritis